High cardiac troponin I plasma concentration in a calf with myocarditis - Karapinar, Tolga; Dabak, Durrin Ozlem; Kuloglu, Tuncay; Bulut, Hakan (Canadian Vet Med Assoc, 2010)
A 15-day-old Brown Swiss calf, whose clam had suffered from foot-and-mouth disease, was presented with a history of depression and failure to suckle The calf had an irregular cardiac rhythm and increased plasma cardiac troponin I (cTnI) detected with a commercial human immunoassay The calf cited the following day and myocardiris was detected The cTnI assay may be useful in diagnosis of myocarditis in cattle
Keywords: Mouth-Disease Virus; Creatine-Kinase-Mb; Ventricular-Tachycardia; Skeletal-Muscle; Infarction; Pericarditis; Diagnosis; Markers; Cattle; Horse